Identificación de la presencia de macracanthorhynchus hirudinaceus en cerdos faenados en camales de la provincia de Bolívar - Haro Bautista, Alan Moisés (2025)
Macracanthorhynchus hirudinaceus was an intestinal parasite belonging to the phylum Acanthocephala, responsible for the zoonosis known as macracanthorhynchosis, which affected mainly pigs and, occasionally, humans. Its life cycle was indirect, using coprophagous beetles of the Scarabaeidae family as intermediate hosts, within which it reached the infective stage called cystocanthus. Pigs were infected by ingesting these beetles, which allowed the parasite to attach itself to the small intestine by means of its hooked proboscis, causing enteritis, peritonitis and, in some cases, intestinal perforations. To identify its presence, 80 slaughtered pigs were selected, distributed in four cantons of the province of Bolivar: Guaranda, Chimbo, Echeandía and Las Naves. The study was planned in coordination with the owners of the farms, establishing a protocol that included the collection of samples and parasitological analysis. During post-mortem inspection, the small intestines (duodenum, jejunum) were removed in order to detect the presence of the parasite. Likewise, stool samples were taken directly from the rectum for coproparasitic analysis using macroscopic and microscopic techniques, which allowed the identification and classification of parasites and eggs, as well as the evaluation of possible tissue damage. Variables such as incidence, prevalence, intensity of infection and the different stages of parasite development were measured. Host characteristics such as age, origin and physical condition were also analyzed. The information collected was interpreted by means of descriptive and comparative analyses, which allowed establishing correlations between the presence of the parasite and the associated factors. This study provided relevant data on the parasitic situation in the region, allowing the generation of useful knowledge for the implementation of control, prevention and sanitary improvement measures in local swine production.